Comparison of Learning Outcomes Using Models Media Assisted Problem Based Learning on Materials Supporting Solution Class XI Senior High School - Yossie Juliastri Napitupulu; Jasmidi Jasmidi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
The aim of this study was to find out the differences in student learning outcomes taught using the Problem Based Learning (PBL) model using Powtoon media and Powerpoint media. This method of research is a quasi-experimental research with a non-equivalent control group design. The research sample was taken randomly from a homogeneous population, namely 2 classes XI MIA 2 and XI MIA 3 with a total of 64 students.The N-gain result for the experimental class I was 0.73% and for the experimental class II was 0.63%, based on the results of the experimental class I which was included in the high category. It was obtained that the average value of student learning outcomes in experimental class I was 84.38 while in experimental class II was 77.81 so that there was a significant difference in the value of student learning outcomes using the Problem Based Learning learning model assisted by Powtoon and Powerpoint media.